Enhancing Citizen Engagement in Public Service Delivery - Luangprapat, Wasan; Pungprawat, Kriangchai; Chaiyachit, Chai (King Prajadhipok’s Institute Journal, 2024)
Citizen-centric public service delivery has been mainstreamed in worldwide public sector reform. This applied research aims to develop an institutional framework and appropriate citizen engagement toolkits for the Thai public sector. The research was carried out qualitatively. Data were primarily taken from documents on emerging trends in citizen engagement in global practice and some case studies. Findings revealed that the administrative agencies perform various functions in government services. Thus, to advance proper participatory programs, we need to consider different types of citizen engagement, which vary according to the nature of this kind of function. We create a typology of three citizen engagement models, including (1) co-governance that is suitable for policy administration, (2) co-management that is suitable for supporting, supervising, regulating, licensing, and adjudicating disputes functions, (3) co-production that is suitable for providing services function.